Preventing Bullying in Pesantren: A Maqāṣid al-Sharī‘ah and Hadith Perspective on the Role of the Sakinah Family - Irsyad Hasan; Marwan Mas'ud; Teguh Dwi Prayoga (LPPPM STAI Darul Hikmah Bangkalan, 2026)
This study examines the concept of the sakinah family as a preventive framework against bullying from a hadith-based perspective. Employing a qualitative library research design, the primary data sources consist of canonical hadith collections—particularly Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Sunan Abī Dāwūd, and Sunan al-Tirmidhī—. Secondary sources include contemporary scholarly works on bullying, child psychology, and Islamic family studies published in peer-reviewed journals. Using thematic hadith analysis (al-dirāsah al-mawḍū‘iyyah) and a socio-normative approach, this study identifies four operative mechanisms through which the sakinah family model functions in preventing bullying: (1) the internalization of compassion (raḥmah) through prophetic parenting patterns, (2) the cultivation of emotional regulation based on the prohibition of anger-driven aggression, (3) dialogical conflict resolution modeled in the Prophet’s household interactions, and (4) moral-social accountability reinforced through teachings on dignity (karāmah) and the prohibition of humiliation. These mechanisms operate at the levels of character formation, emotional development, and social behavior control within the family structure. The novelty of this research lies in its analytical reconstruction of hadith narratives into a concrete preventive model against bullying, moving beyond general normative discussions of the sakinah family toward a structured socio-ethical framework grounded in prophetic traditions. By bridging classical hadith scholarship and contemporary bullying discourse, this study offers a conceptually integrative and practically applicable contribution to Islamic family studies